Metformin influences drug sensitivity in pancreatic cancer cells. (May 2018) - Candido, Saverio; Abrams, Stephen L.; Steelman, Linda; Lertpiriyapong, Kvin; Martelli, Alberto M.; Cocco, Lucio; Ratti, Stefano; Follo, Matilde Y.; Murata, Ramiro M.; Rosalen, Pedro L.; Lombardi, Paolo; Montalto, Giuseppe; et al.
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an aggressive, highly metastatic malignancy and accounts for 85% of pancreatic cancers. PDAC patients have poor prognosis with a five-year survival of only 5–10% after diagnosis and treatment. Pancreatic cancer has been associated with type II diabetes as the frequency of recently diagnosed diabetics that develop pancreatic cancer within a 10-year period of initial diagnosis of diabetes in increased in comparison to non-diabetic patients. Metformin is a very frequently prescribed drug used to treat type II diabetes. Metformin acts in part by stimulating AMP-kinase (AMPK) and results in the suppression of mTORC1 activity and the induction of autophagy. In the following studies, we have examined the effects of metformin in the presence of various chemotherapeutic drugs, signal transduction inhibitors and natural products on the growth of three different PDAC lines. Metformin, by itself, was not effective at suppressing growth of the pancreatic cancer cell lines at concentration less than 1000 nM, however, in certain PDAC lines, a suboptimal dose of metformin (250 nM) potentiated the effects of various chemotherapeutic drugs used to treat pancreatic cancer ( e.g ., gemcitabine, cisplatin, 5-fluorouracil) and other cancer types ( e.g ., doxorubicin, docetaxel). Furthermore, metformin could increase anti-proliferative effects of mTORC1 and PI3K/mTOR inhibitors as well as natural products such as berberine and the anti-malarial drug chloroquine in certain PDAC lines. Thus, metformin can enhance the effects of certain drugs and signal transduction inhibitors which are used to treat pancreatic and various other cancers.